Uncovering The Secret Of Adam Lang As A Former BritishPrime Minister In Roman Polanski's The Ghost WriterMovie (2010): A Sociological Approach - Mahendra, Dendy; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi,S.S. M. Hum (2015)
The research is proposed to analyze the uncovering the secret of Adam Lang as a former British prime minister in Roman Polanski's The Ghost Writer movie with Sociological Approach. There are two objectives analysis: first, is to analyze the novel in term of structural elements, and the second is to analyze the novel based on Sociological Approach. This study is a descriptive qualitative study, using The Ghost Writer movie as the object of analysis. There are two kinds of data sources use in the analyzing, namely primary and secondary data sources. The primary data is the movie itself and the secondary data sources are some books, internet, and articles related to the subject. The technique of data collection in this research is library research by summarizing, paraphrasing, and documenting the data. In analyzing the data, the researcher employs descriptive qualitative analysis. In this study, the researcher gets some conclusion as follows. Firstly, based on the structural analysis, it is evidence that in The Ghost Writer movie, the unnamed The Ghost work professionally just to find the truth based on humanity although he die in the end of the story . Secondly, based on the sociological analysis also reflects the social condition of Poland society in the first half of twentieth century.